Kecerdasan Logis Matematis Siswa melalui Model Pembelajaran Berbasis Proyek di SMA - Decy Pramita Sari Yusna; Bahrun Bahrun; M. Duskri (Didaktik Matematika, 2019)
This research aimed is to describe students' logical-mathematical intelligence through project-based learning. This study was descriptive qualitative research. Participants in this research are students of class XI school in Meulaboh for one class that is class XI-1. The data is students answer that was obtained from the logical-mathematical intelligence test. The data collected by using multiple intelligence tests and student answers results obtained from the task of logical-mathematical intelligence during the project-based learning process. The results show that in general logical-mathematical intelligence during project-based learning each group meets a minimum of four out of five aspects of logical-mathematical intelligence. Thus, the logical-mathematical intelligence of students developing after the implementation of the project-based learning.